Breast reconstruction with autologous tissue following mastectomy: two case reports of a delayed conventional transverse rectus abdominismyocutaneous (TRAM) and latissimus dorsi myocutaneous (LDM) flap surgery - Seswandhana, Rosadi; Wicaksana, Aditya; Wahdini, Siti Isya; Dachlan, Ishandono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Breast cancer is the most common malignant tumor and the leading cause of death among females. Most women with breast cancer will undergo breast-conserving surgery (BCS) or lumpectomy, simple or total mastectomy, modified radical mastectomy or bilateral mastectomy. Breast reconstruction solves many of the problems. The goal is to return the patient to a near-normal state so that she is not handicapped in her daily living. Breast reconstruction is also intended to offer psychological benefits to women treated by mastectomy following a diagnosis of possibly terminal cancer. In these case reports, we reported two successful cosmetic reconstruction cases. The first case was a 39-years-old female with non-recurrent breast cancer consulted and was referred by the oncology surgeon to the Plastic Reconstructive, and Aesthetic Surgery Division, Department of Surgery, Dr. Sardjito General Hospital. She wanted to undergo breast reconstruction. We planned to operate three years following mastectomy. She was diagnosed with 3B-stage of right breast cancer before. After the surgery, the patient received six series of chemotherapy. She also underwent radiotherapy 25 times and hormonal therapy. We decided to perform a transverse rectus abdominis myocutaneous (TRAM) flap surgery on her with 22 months follow up. The procedure provided good results, and the patient was satisfied. The second case was a 32-year-old woman who after excision of a phyllodes tumor and wanted breast reconstruction. Reconstruction was performed four years after tumor removal using latissimus dorsi myocutaneous (LDM) flap. The surgery provided good results, and the patient was satisfied. We reported two successful cosmetic reconstruction cases of non-recurrent 3B-stage of right breast cancer post-mastectomy after pedicled TRAM flap surgery and left breast post excision of phyllodes tumor after LDM flap surgery.